Dopamine-related receptors, substance dependence, behavioral problems and personality among juvenile delinquents. (1st February 2021) - Ruchkin, Vladislav; Koposov, Roman; Oreland, Lars; af.Klinteberg, Britt; Grigorenko, Elena L.
Highlights: COMT rs737865 GG genotype associated with increased risk of substance dependence. Results highlight a role of the DRD4 C_1, 611, 535 GG genotype in substance dependence. DRD4 C_1, 611, 535 GG genotype associated with antisocial personality disturbances. Multi-polymorphism/haplotype-based approach to variability in a single gene used. Abstract: The objective was two-fold: to examine possible associations between dopamine-related genetic polymorphisms and (1) substance dependence; and (2) self-reported psychiatric disturbances, behavioral problems, and personality. Genotyping of single nucleotide polymorphisms (SNP: s) in COMT, DAT and DRD4 was conducted in 174 Russian male juvenile inmates (14–18 years of age) subdivided into having a diagnosis of substance dependence or not, as assessed by using K-SADS-PL. The inmates completed several self-reports assessing psychiatric symptoms (CPTS-RI, BDI), behavioral problems (YSR), and personality traits (TCI). Results revealed that juveniles meeting the criteria for substance dependence differed significantly from their counterparts in four polymorphisms, namely COMT rs737865, DAT rs6347, DRD4 C_1611535 and DRD4 exon III; and exact binary regression analysis indicated a highly significant association between the DRD4 C_1611535 GG genotype and substance dependence. One-way ANOVA tests further showed this gene polymorphism variant to be significantly associated with higher levels of posttraumatic stress, thought problems, aggressive behavior, and personality traits indicating antisocial personality disturbances, as compared with the other gene polymorphism variants. In conclusion, the results underscore the role of the DRD4 polymorphism C_1611535 GG genotype for substance dependence, and suggest its associations with different self-reported phenotype characteristics.